Effects of particle size in silica sol on the mechanical and thermal properties of SiO2f/SiO2 composites. Issue 3 (12th December 2022) - Ding, Donghai; Li, Jie; Li, Runan; Zhang, Li; Hou, Chen; Xiao, Guoqing; Chong, Xiaochuan; Luo, Jiyuan; Deng, Peilin
Abstract: In this paper, quartz fiber‐reinforced silica matrix SiO2f /SiO2 composites were prepared by the precursor impregnation‐heat treatment method using quartz fiber needle felt as the reinforcement and silica sol as the precursor. The effects of particle size in silica sol (10, 50, and 100 nm) on the density, apparent porosity, mechanical properties, and thermal properties of SiO2f /SiO2 composites were investigated. The phase composition and microstructure of the composites were characterized by X‐ray diffraction and scanning electron microscopy, respectively. The thermal expansion coefficient and thermal conductivity of composites were measured by a push rod method and the laser method. The results show that the density, apparent porosity, and mechanical strength of the specimens firstly increase and then decrease with the increase in the particle size in silica sol. The sample using silica sol with particle size 50 nm has the optimum overall performances (i.e., the flexural strength of 13.7 MPa and the compressive strength of 59.8 MPa), and shows a ductile fracture behavior. At 300°C–700°C, the average thermal expansion coefficient of the optimal sample is .783 × 10 −6 /°C. And the thermal conductivity of the samples increases with the increase in temperature, and it reached the highest value of .810 W/(m·K) at 700°C. The SiO2f /SiO2 composites show obvious advantages in the application of load‐bearing and thermal insulation integration, and they are expected to meet the demanding requirements of hot‐pressing sintering and non‐ferrous metallurgy industries.